2023
DOI: 10.3390/pharmaceutics15010299
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Tacrolimus Based on Volumetric Absorptive Microsampling Technique (VAMS) in Renal Transplant Pediatric Recipients—LC-MS/MS Method Development, Hematocrit Effect Evaluation, and Clinical Application

Abstract: Tacrolimus (TAC) is post-transplant pharmacotherapy’s most widely used immunosuppressant. In routine clinical practice, frequent uncomfortable venipuncture is necessary for whole-blood (WB) collection to check trough TAC levels. Volumetric absorptive microsampling (VAMS) is an alternative strategy to WB collection. In this study, we aimed to validate and develop a liquid chromatography–tandem mass spectrometry (LC-MS/MS) method for TAC quantification in WB and VAMS samples. After extraction with water and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Some studies have reported that 24 h is a suitable time for drying VAMS samplers under ambient conditions. In our study about TAC [18], a reduction in the drying time to 1 h ensures a high recovery of TAC and no significant differences between the 2 h and 1 h period of VAMS drying. Vethe et al [19] reported that 3 h of VAMS drying is satisfactory; however, Kita et al [20,21] and Koster et al [22] reported that the period of drying VAMS may be reduced to 2 h with no significant differences in TAC extraction accuracy.…”
Section: Samplingmentioning
confidence: 67%
“…Some studies have reported that 24 h is a suitable time for drying VAMS samplers under ambient conditions. In our study about TAC [18], a reduction in the drying time to 1 h ensures a high recovery of TAC and no significant differences between the 2 h and 1 h period of VAMS drying. Vethe et al [19] reported that 3 h of VAMS drying is satisfactory; however, Kita et al [20,21] and Koster et al [22] reported that the period of drying VAMS may be reduced to 2 h with no significant differences in TAC extraction accuracy.…”
Section: Samplingmentioning
confidence: 67%
“… Technique Matrix LOD (ng/mL) Dynamic range (ng/mL) Ref. Coupling of solid-phase microextraction to mass spectrometry Whole blood 0.3 1–50 [ 47 ] UHPLC Pharmaceutical Formulation 1.0 × 10 5 –3.0 × 10 5 [ 15 ] LC/MS Plasma 0.01 0.01–2 [ 11 ] LC-MS/MS Whole blood 1–40 [ 12 ] LC-MS/MS Whole blood 0.5–60 [ 13 ] UPLC-MS/MS Whole blood 50–5000 [ 16 ] HPLC-MS/MS Whole blood 2.25–42.9 [ 50 ] Millifluidic microwave Whole blood 0.00012 10–500 [ 51 ] Microwave Blood 0.032 [ 52 ] Immunoassay Blood ...…”
Section: Resultsmentioning
confidence: 99%
“…So far, numerous analytical methods have been used for the quantification of Tac, such as liquid chromatography tandem mass spectrometry (LC-MS/MS) [ [10] , [11] , [12] , [13] ], ultra-high performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) [ [14] , [15] , [16] ], UHPLC [ 17 ], enzyme-linked immunosorbent assay (ELISA) [ 18 ], enzyme multiplied immunoassay technique (EMIT) [ 19 ], automated microparticle enzyme immunoassay (MEIA) [ 20 ], electro-chemiluminescence immunoassay (ECLIA) [ 21 ], fluorescent aptasensor [ 22 ], and electrochemical immunosensor [ 9 ]. Some of these methods require extensive training, a high degree of technical ability, a time-consuming process, and high-cost sophisticated equipment, which are the main drawbacks for rapid and real-time routine quantifications [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the application of microsampling in routine clinical pharmacology is still limited [19,20], mainly because of the need for instrumentation capable of quantifying analytes in very small volumes with sufficient sensitivity, such as liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS), which are found only in specialized centers. LC-MS/MS instrumentation is sensitive enough to enable microsample drug assays and has already enabled their application in routine practice [21], for example, for immunosuppressants [6,20,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the application of microsampling in routine clinical pharmacology is still limited [19,20], mainly because of the need for instrumentation capable of quantifying analytes in very small volumes with sufficient sensitivity, such as liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS), which are found only in specialized centers. LC-MS/MS instrumentation is sensitive enough to enable microsample drug assays and has already enabled their application in routine practice [21], for example, for immunosuppressants [6,20,[22][23][24]. Automated dried spot processing devices directly coupled to an LC-MS system with integrated direct elution and extraction steps [25,26] have been successfully applied to the analysis of many drugs, such as antiretrovirals [27], antimycotics [28,29], and antiepileptics [30].…”
Section: Introductionmentioning
confidence: 99%